2020
DOI: 10.3390/ijms21041248
|View full text |Cite
|
Sign up to set email alerts
|

NCAPG Dynamically Coordinates the Myogenesis of Fetal Bovine Tissue by Adjusting Chromatin Accessibility

Abstract: NCAPG is a subunit of condensin I that plays a crucial role in chromatin condensation during mitosis. NCAPG has been demonstrated to be associated with farm animal growth traits. However, its role in regulating myoblast differentiation is still unclear. We used myoblasts derived from fetal bovine tissue as an in vitro model and found that NCAPG was expressed during myogenic differentiation in the cytoplasm and nucleus. Silencing NCAPG prolonged the mitosis and impaired the differentiation due to increased myob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 49 publications
2
14
0
Order By: Relevance
“…Biological and functional validation, including molecular function, in vitro, and in vivo studies, is critical for supporting GWAS results 34 and guiding the planning of follow‐up. In the present study, we attempted to verify an identified candidate gene in an in vitro functional study with proliferation and myogenic differentiation assays demonstrated to be reliable in vitro tools with which to investigate skeletal muscle development 50‐52 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological and functional validation, including molecular function, in vitro, and in vivo studies, is critical for supporting GWAS results 34 and guiding the planning of follow‐up. In the present study, we attempted to verify an identified candidate gene in an in vitro functional study with proliferation and myogenic differentiation assays demonstrated to be reliable in vitro tools with which to investigate skeletal muscle development 50‐52 …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we attempted to verify an identified candidate gene in an in vitro functional study with proliferation and myogenic differentiation assays demonstrated to be reliable in vitro tools with which to investigate skeletal muscle development. [50][51][52] factors. 7 MTPN was identified originally in a hypertensive rat heart model and has been shown to regulate growth of myocardial cells.…”
Section: Biological Function Validation Is Important In Post-gwas Studymentioning
confidence: 99%
“…NCAPG (non SMC condensin I complex subunit G) is a subunit of the lectin complex which is responsible for the concentration and stability of chromosomes during mitosis and meiosis and protein phosphorylation activation polysaccharide composition [7,8]. The dysregulation of NCAPG was associated with the occurrence of many diseases, including endometrial mixed adenocarcinoma and croup.…”
Section: Introductionmentioning
confidence: 99%
“…NCAPG may promote the occurrence and development of tumors by regulating the cell cycle, cell aging and mismatch repair [8]. NCAPG de ciency increases apoptosis and inhibits tumor cell proliferation [9]. Previous studies have shown that NCAPG is highly expressed in many malignant tumors, such as gastric cancer, liver cancer, glioma, and prostate cancer, and its expression level is closely related to the poor prognosis of the tumors [10][11][12].…”
Section: Introductionmentioning
confidence: 99%